Unit BOD Load of Cooked Food Waste - HASEGAWA, Reiko; MORI, Motoko; FUNASAKA, Ryozo; OSE, Youki (Journal of Home Economics of Japan, 1990)
In Japan, water quality has been improving gradually year by year, but recently the tendency has been retarded by the increased input of gray-water, especially cooked food waste. Untreated cooked food waste disposed directly into the river through street gutters, is decomposed in the river and plays an important ingredient as BOD materials. The authors tabulated the BOD per unit g of food for 99 kinds of uncooked foods and 33 kinds of cooked foods to estimate the BOD load for each type of food waste, together with carbon tetrachroride extractable materials, ignition loss and water contents. Simple and significant correlation between BOD and ignition loss was obtained when both variables were expressed in logarithmic forms : ln y=0.913 ln x +0.448 (γ=0.865), where y, BOD expressed as ppm; x, ignition loss ex pressed as %. Correlation coefficient between measured and predicted BOD was significant at 1% (γ=0.865), and the BOD of food, whose value was not determined, will be estimated from the above equation by using the ignition loss. The agreement between the calculated and determined BOD values was found for the food listed in “The Japan Standard Food Composition Table, ” and it is thought that BOD value of food can be estimated from the above equation.